2020
DOI: 10.3341/kjo.2019.0113
|View full text |Cite
|
Sign up to set email alerts
|

Macular Microvasculature in High Myopia without Pathologic Changes: An Optical Coherence Tomography Angiography Study

Abstract: To investigate macular microvasculature changes using optical coherence tomography angiography (OCTA) and analyze their correlation with the structural parameters in highly myopic eyes. Methods: We measured the area of the foveal avascular zone (FAZ) and the parafoveal vessel density in the superficial and deep retinal plexuses using OCTA. The magnification effect of the FAZ area was corrected using Bennett's formula. Retinal thickness measured at each corresponding area of the OCTA parameters, subfoveal choro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
1
26
1
1
Order By: Relevance
“…[18] and Min et al [19] found that the FAZ area of highly myopic eyes was larger than that of emmetropic eyes, and it was positively correlated with the eye axis, which is contrary to our research results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[18] and Min et al [19] found that the FAZ area of highly myopic eyes was larger than that of emmetropic eyes, and it was positively correlated with the eye axis, which is contrary to our research results.…”
Section: Discussioncontrasting
confidence: 99%
“…The deep central fovea blood ow density is most closely related to the loss of retinal capillaries related to myopia and can be used as a sensitive indicator for detecting capillary loss in high myopia. Min et al [19] found that parafoveal vessel density was decreased and the super cial capillary plexus was signi cantly reduced in patients with high myopia without pathological changes, while there was no signi cant difference in the deep parafoveal vessel density [7] . In a prospective study, Venkatesh et al [26] found that deep blood vessel density changes in the macular area of simple high myopia were positively correlated with AL and negatively correlated with myopic SE, while the super cial blood vessel density was not signi cantly correlated with AL or myopic SE.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed no significant difference in the foveal avascular zone (FAZ) area between myopic and control groups, consistent with our results 14 , 15 . Min et al, in contrast, concluded that the FAZ area was significantly larger in the myopic eyes 16 . Since different OCTA devices use different technologies and patients are of different ages, sexes, and ethnicities, it is not possible to standardize measurements.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple studies have demonstrated decreasing macular VD being associated with increasing myopia [ 21 , 22 ]. Some studies have demonstrated only differences in certain regions and layers [ 23 , 24 ], whilst others have not demonstrated any differences between high myopic and non-high myopic patients [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%